Quantitative Chemical Proteomics Reveals Resveratrol Inhibition of A549 Cell Migration Through Binding Multiple Targets to Regulate Cytoskeletal Remodeling and Suppress EMT - Chen, Xiao; Wang, Yutong; Tian, Jing; Shao, Yurou; Zhu, Bo; Wang, Jigang; Hua, Zichun (Frontiers in Pharmacology, 2021)
Resveratrol (RSV), a health-promoting natural product, has been shown to affect various cellular processes in tumor cells. However, the specific protein targets of RSV and the mechanism of action (MOA) of its anticancer effect remain elusive. In this study, the pharmacological activity of RSV was first evaluated in A549 cells, and the results showed that RSV significantly inhibited A549 cell migration but did not affect cell viability. To elucidate the underlying mechanism, a quantitative chemical proteomics approach was employed to identify the protein targets of RSV. A total of 38 target proteins were identified, and proteomic analysis showed that the targets were mainly involved in cytoskeletal remodeling and EMT, which were verified by subsequent in vitro and in vivo assays. In conclusion, RSV inhibits A549 cell migration by binding to multiple targets to regulate cytoskeletal remodeling and suppress EMT.